2017
DOI: 10.4236/ojanes.2017.79030
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Effect of Intravenous Lidocaine Infusion, Gabapentin and Their Combination on Postoperative Analgesia after Thyroid Surgery

Abstract: Objective: This prospective randomized study aimed to evaluate the effect of IV lidocaine infusion or gabapentin and their combination in providing efficient analgesia after thyroid surgery. Methods: Eighty-eight patients scheduled for thyroidectomy were randomized into four equal groups (n = 22).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Previous studies have found that intravenous infusion of lignocaine attenuates haemodynamic response associated with intubation and extubation of trachea ( 1 , 5 - 8 ). The combination of verapamil with lignocaine ( 7 ) and also drugs like diltiazem ( 6 ) have also found to attenuate haemodynamic response. Many previous studies show lignocaine infusion being used for postoperative pain relief ( 9 - 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that intravenous infusion of lignocaine attenuates haemodynamic response associated with intubation and extubation of trachea ( 1 , 5 - 8 ). The combination of verapamil with lignocaine ( 7 ) and also drugs like diltiazem ( 6 ) have also found to attenuate haemodynamic response. Many previous studies show lignocaine infusion being used for postoperative pain relief ( 9 - 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many drugs have been recommended for the attenuation of haemodynamic response during intubation and extubation of the trachea like remifentanil ( 1 ), lidocaine ( 2 ), magnesium sulfate ( 3 ), clonidine ( 4 ) esmolol ( 5 ), and dexmedetomidine ( 6 ). Recent studies have demonstrated that perioperative lignocaine infusion is also useful in reducing postoperative pain ( 7 - 10 ). Very few previous studies have demonstrated both the effect of lignocaine infusion that is attenuation of haemodynamic response to intubation and extubation of trachea and postoperative analgesia ( 11 - 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pain severity is subjective and highly variable, and it is important to ameliorate pain. The aim of postoperative pain control is to reduce the pain felt by the patient, and various studies have been performed for the reduction of post-thyroidectomy pain 2,10,15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine has analgesic, antihyperalgesic, and anti-inflammatory properties and thus has many beneficial effects in many surgeries 7,8 . Several studies have shown that intravenous IV lidocaine use in the intraoperative period reduces postoperative pain [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…A sum of 11 RCTs [17][18][19][29][30][31][32][33][34][35][36] with 761 patients involved in the meta-analysis (381 in Lido group and 380 in Con group). Out of these RCTs, six studies were published in English [17][18][19][29][30][31] and ve in Chinese [32][33][34][35][36]. The year of publication ranged from 2014 to 2022; the main ASA status was I-II, and only one study involved patients ranked as ASA III [17].…”
Section: Study Characteristicsmentioning
confidence: 99%